IMAJINASI KEBANGSAAN ORANG JAWA DI SURINAME DALAM VIDEO MUSIK POPULER - Adji, Titus Soepono (Capture : Jurnal Seni Media Rekam, 2009)
In nowadays context, Javanese people in Suriname seems to be something un expectable. They have been living far away from the mother land since a century ago. This kind condition not only restricted the communication within their ancestors but loose also the access into their cultural and identity references. Who really am I? Where did I Come from ? and What is my goal here? There are some frequent questions. Following the technology, here , is internet , we now able to see that Javanese people in Suriname can say the origin of their Javanese identity. Is it a deconstruction ? or a reflexive media to show their origin identity. Keyword : Javanese, Suriname, identity